Iron mineral dissolution releases iron and associated organic carbon during permafrost thaw - Patzner, Monique S.; Mueller, Carsten W.; Malusova, Miroslava; Baur, Moritz; Nikeleit, Verena; Scholten, Thomas; Hoeschen, Carmen; Byrne, James M.; Borch, Thomas; Kappler, Andreas; Bryce, Casey (Nature communications, 2020)
It has been shown that reactive soil minerals, specifically iron(III) (oxyhydr)oxides, can trap organic carbon in soils overlying intact permafrost, and may limit carbon mobilization and degradation as it is observed in other environments. However, the use of iron(III)-bearing minerals as terminal electron acceptors in permafrost environments, and thus their stability and capacity to prevent carbon mobilization during permafrost thaw, is poorly understood. We have followed the dynamic interactions between iron and carbon using a space-for-time approach across a thaw gradient in Abisko (Sweden), where wetlands are expanding rapidly due to permafrost thaw. We show through bulk (selective extractions, EXAFS) and nanoscale analysis (correlative SEM and nanoSIMS) that organic carbon is bound to reactive Fe primarily in the transition between organic and mineral horizons in palsa underlain by intact permafrost (41.8 ± 10.8 mg carbon per g soil, 9.9 to 14.8% of total soil organic carbon). During permafrost thaw, water-logging and O 2 limitation lead to reducing conditions and an increase in abundance of Fe(III)-reducing bacteria which favor mineral dissolution and drive mobilization of both iron and carbon along the thaw gradient. By providing a terminal electron acceptor, this rusty carbon sink is effectively destroyed along the thaw gradient and cannot prevent carbon release with thaw. Iron minerals trap carbon in permafrost, preventing microbial degradation and release to the atmosphere as CO 2 , but the stability of this carbon as permafrost thaws is unclear. Here the authors use nanoscale analyses to show that thaw conditions stimulate Fe-reducing bacteria that trigger carbon release.